2005
DOI: 10.1177/107906320501700403
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Attrition as Indicators for Program Improvement not Offender Shortcomings: A Study of Sex Offender Treatment Attrition

Abstract: This study classified potential attrition predictors under the domains of risk, need and responsivity (D. Andrews & J. Bonta, 2003). Non-sexual criminogenic needs (e.g. aggression, rule violating behaviors) and responsivity factors (e.g. lack of motivation and denial) were the two main clusters of predictors that correctly classified 95.3% of program completers and non-completers using discriminant function analysis in a sample of high-risk male sexual offenders treated in an accredited inpatient sex offender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 29 publications
6
84
0
4
Order By: Relevance
“…Taken together, these results suggest that the programme was designed and delivered in a manner that accommodated the challenges of retaining these men in treatment. As Beyko and Wong (2005) imply, if the programme was not responsive in this way, it would be left with few participants. Two additional sources of information support this argument: (a) the low rate of therapist-initiated expulsions suggests that programme staff saw it as their responsibility to retain difficult clients; and (b) the average stay of nearly 3 months for noncompleters suggests that decisions to leave were not taken lightly by therapists or offenders.…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, these results suggest that the programme was designed and delivered in a manner that accommodated the challenges of retaining these men in treatment. As Beyko and Wong (2005) imply, if the programme was not responsive in this way, it would be left with few participants. Two additional sources of information support this argument: (a) the low rate of therapist-initiated expulsions suggests that programme staff saw it as their responsibility to retain difficult clients; and (b) the average stay of nearly 3 months for noncompleters suggests that decisions to leave were not taken lightly by therapists or offenders.…”
Section: Discussionmentioning
confidence: 93%
“…Results of a meta-analysis conducted by Olver, Stockdale, and Wormith (2011), which includes more than 120 studies and 41,000 offenders, confirms this finding across multiple intervention types to show that treatment attrition is associated with increased odds of recidivism. Specifically, studies have found that program attrition is related to increased reoffending for adult sex offenders (Beyko & Wong, 2005;Marques, Day, Nelson, & West, 1994;Wormith & Olver, 2002), domestic violence offenders (Daly & Pelowski, 2000), violent offenders (Polaschek, 2011), and drug abusers (Hiller, Knight, & Simpson, 1999a, 1999bLang & Belenko, 2000;Mateyoke-Scrivner, Webster, Staton, & Leukfeld, 2004) and for offenders in general treatment programs (Bouffard & Muftic, 2006;Hatcher, McGuire, Bilby, Palmer, & Hollin, 2012). The literature analyzing juvenile offenders confirms those findings to show that delinquents who fail to complete sex offender (Edwards et al, 2005;Hunter & Figueredo, 1999;Worling & Curwen, 2000) and substance abuse treatment (Hser et al, 2001;Williams & Chang, 2000) are also more likely to reoffend.…”
Section: The Relationship Between Treatment Attrition and Juvenile Rementioning
confidence: 66%
“…Because participants in this study reported benefit from therapy, this sample undoubtedly differs from sex offenders who had no opportunity to receive therapy or dropped out. Failure to engage in therapy is a known predictor of sex offender treatment attrition (Beyko & Wong, 2005). We are cognizant that some sex offenders refuse, or deny the need for, treatment, such as the "repeat offender" and "the pretender" described by Jones and Lawson (2012).…”
Section: Limitations and Strengthsmentioning
confidence: 98%